Tissue culture and biolistic–mediated transformation of Impatiens balsamina - Mohd. Taha, Aishah (2008)
Biolistic-mediated transformation is an approach to transfer a gene of interest into a plant cell using particle bombardment method. Tissue culture experiment was conducted to optimize shoot regeneration from cotyledon explant of 7 day-old seedlings I. balsamina. The maximum average number of shoots (6.8 ± 1.05 shoots) per explant was obtained on full strength MS-based medium containing 1 mg/L BAP after three weeks of culture. For rooting induction, there was no significant difference on percentage of root regeneration on full strength (84%-94%) and half strength MS–based medium (78%-96%) supplemented with IAA (0.1 - 1mg/L), IBA (0.5 - 2 mg/L) and NAA (0.1 - 1 mg/L) after two weeks of culture. Plantlets were successfully produced on full strength MS plates supplemented with 1 mg/L BAP (93%) for shooting and half strength MS media supplemented with 0.1 mg/L IAA (92%) for rooting in eight-week culture. Biolistic technique was used for the transformation of uidA and hph genes into I. balsamina. The 7 day- old cotyledons explants were bombarded with pRQ6 containing uidA gene encode for ß-glucuronidase (GUS) and hph gene conferring resistance to hygromycin and co-transformation was carried out using pRQ6 with pAHG11 (contain bar gene conferring resistance to herbicide Basta). The physical and biological factors of bombardment such as target distance (6 - 12 cm), helium pressure (650 - 1100 psi), number of bombardments (once and twice), DNA concentrations (0.5 - 1.5µg), preculture times (4 - 32h), osmotic treatments using mannitol , sorbitol and combination of mannitol and sorbitol at 0.2 M, 0.4 M and 0.6 M and post-bombardment incubation times (4 - 48 h) were optimized. Transformation of I. balsamina with pRQ6 and cotransformed with pRQ6 and pAHG11 at 28 mm Hg vacuum using optimized bombardment conditions (9 cm target distance, 1100 psi helium pressure, one time bombardment, 1.0 µg DNA, 16 h pre-culture time with osmotic treatment of 0.4 M mannitol and sorbitol and 24 h post-bombardment incubation time) showed the highest average number of GUS spots of 149.3 and 128.1, respectively. Delay selection method was used to delay the timing of selection on shooted explants after bombardment to obtain transformed plants. Out of 160 bombarded explants with pRQ6, only 84 plants were successfully regenerated from selected 35-day old shooted explants after five weeks grown on MS –based medium containing 75 mg/L hygromycin. All regenerated plants (84 plants) were GUS positive. However, there was no plant regenerated on MSbased medium containing 1 mg/L phosphinothricin (PPT) after co-transformed with pRQ6 and pAHG11. Furthermore, PCR results showed only 14 of 40 GUS positive plants survived at 75 mg/L hygromycin were hph gene positive. In conclusion, the PCR results also showed the possibility integration of hph gene into the genomic DNA of transformed plants.